Bakteri Tanah Di Sekitar Rhizosfer Tumbuhan Pioner Pada Lahan Bekas Tambang Kapur - Sriwulan Sriwulan; Riska Andriani; Susanti Dhini Anggraini; Hesti Kurniahu; Annisa Rahmawati (Universitas Muhammadiyah Surakarta, 2022)
Pioneer plants are plants with high adaptability, so they can grow in disturbed environments, such as ex-limestone mining areas. This adaptability is supported by the ability of these plants to associate with soil bacteria in their rhizosphere area. The presence of these bacteria can support the growth of pioneer plants on disturbed land. The purpose of this study was to characterize the soil bacteria around the rhizosphere of pioneer plants in the former limestone mining areas. Soil samples in the rhizosphere area of 5 pioneer plants from ex-mining lime were then isolated using the Pour plate method to obtain bacterial isolates. The bacterial isolates obtained were then identified their colony morphology. Based on the results of colony morphological identification, 21 isolates were obtained from the rhizosphere of 5 pioneer plants from the former limestone mining area. The highest number of isolates was obtained from the rhizosphere of the Waltheria indica with 9 isolates, 8 isolates of each Lamium barbatum and Digitaria sanguinalis, 7 isolates of Chromoleana odoratum, and 5 isolates of Tridax procumbens.